Consensus on a netball video analysis framework of descriptors and definitions by the netball video analysis consensus group. (8th February 2023) - Mackay, Lois; Jones, Ben; Janse van Rensburg, Dina Christina (Christa); Hall, Francine; Alexander, Lisa; Atkinson, Karen; Baldrey, Pippa; Bedford, Anthony; Cormack, Stuart; Clarke, Jade; Croft, Hayden; Denton, Katie; et al.
Abstract : Using an expert consensus-based approach, a netball video analysis consensus (NVAC) group of researchers and practitioners was formed to develop a video analysis framework of descriptors and definitions of physical, technical and contextual aspects for netball research. The framework aims to improve the consistency of language used within netball investigations. It also aims to guide injury mechanism reporting and identification of injury risk factors. The development of the framework involved a systematic review of the literature and a Delphi process. In conjunction with commercially used descriptors and definitions, 19 studies were used to create the initial framework of key descriptors and definitions in netball. In a two round Delphi method consensus, each expert rated their level of agreement with each of the descriptors and associated definition on a 5-point Likert scale (1—strongly disagree; 2—somewhat disagree; 3—neither agree nor disagree; 4—somewhat agree; 5—strongly agree). The median (IQR) rating of agreement was 5.0 (0.0), 5.0 (0.0) and 5.0 (0.0) for physical, technical and contextual aspects, respectively. The NVAC group recommends usage of the framework when conducting video analysis research in netball. The use of descriptors and definitions will be determined by the nature of the work and can be combined to incorporate further movements and actions used in netball. The framework can be linked with additional data, such as injury surveillance and microtechnology data.